Exploring university students' utilization of AI tools in academic assignments: benefits, challenges, and ethical considerations - Khedher, Akram M Z M; Tarshany, Yasser; Wasiq, Shafiullah; Al-Taei, Mohammad Hameed Ahmed; Alhazmi, Abdulsalam K. (IEEE, 2025)
Artificial Intelligence (AI) has been revolutionizing numerous industries, with education being no exception. Artificial intelligence can transform educational approaches, making them customized, engaging, and effective. This study explores university students' utilization of AI tools in academic assignments, focusing on their benefits, challenges, and ethical considerations. Using a quantitative approach, data were collected through a survey conducted at the International Islamic University Malaysia (IIUM). Findings reveal that students perceive AI tools as valuable for increasing efficiency, understanding complex concepts, and fostering creativity. However, concerns about over-reliance, academic integrity, algorithmic biases, and plagiarism risks were also highlighted. Importantly, students emphasized the need for institutional guidelines and training to promote ethical and effective AI use. The study concludes that a balanced approach to AI integration is essential to ensure its ethical, inclusive, and transparent application in academia. Encouraging collaboration between educators, and AI expert’s system are crucial for restructured design innovative learning environments that fully fit with academic goals and values. This research provides insights for fostering responsible AI adoption in educational practices.